Holocene Climate Variability on the Centennial and Millennial Time Scale - Eun Hee Lee; Dae-Young Lee; Mi-Young Park; Sungeun Kim; Su Jin Park (Journal of Astronomy and Space Sciences, 2014)
There have been many suggestions and much debate about climate variability during the Holocene. However, their complex forcing factors and mechanisms have not yet been clearly identified. In this paper, we have examined the Holocene climate cycles and features based on the wavelet analyses of 14C, 10Be, and 18O records. The wavelet results of the 14C and 10Be data show that the cycles of ~2180-2310, ~970, ~500-520, ~350-360, and ~210-220 years are dominant, and the ~1720 and ~1500 year cycles are relatively weak and subdominant. In particular, the ~2180-2310 year periodicity corresponding to the Hallstatt cycle is constantly significant throughout the Holocene, while the ~970 year cycle corresponding to the Eddy cycle is mainly prominent in the early half of the Holocene. In addition, distinctive signals of the ~210-220 year period corresponding to the de Vries cycle appear recurrently in the wavelet distribution of 14C and 10Be, which coincide with the grand solar minima periods. These de Vries cycle events occurred every ~2270 years on average, implying a connection with the Hallstatt cycle. In contrast, the wavelet results of 18O data show that the cycles of ~1900-2000, ~900-1000, and ~550-560 years are dominant, while the ~2750 and ~2500 year cycles are subdominant. The periods of ~2750, ~2500, and ~1900 years being derived from the 18O records of NGRIP, GRIP and GISP2 ice cores, respectively, are rather longer or shorter than the Hallstatt cycle derived from the 14C and 10Be records. The records of these three sites all show the ~900-1000 year periodicity corresponding to the Eddy cycle in the early half of the Holocene.